Effect of social media interventions on the education and communication among patients with cancer: a systematic review protocol - Alireza Banaye Yazdipour; Sharareh R Niakan Kalhori; Hassan Bostan; Hoorie Masoorian; Elham Ataee; Hasan Sajjadi (BMJ Open, 2022)
Introduction Cancer is a leading cause of death worldwide. In addition, it accounted for approximately 10 million deaths in 2020 alone. Information and communication technologies have great potential for improving health education and communication. Social media is one of the technologies that can help patients with cancer and healthcare providers communicate and provide educational information. Social media are increasingly being used for health promotion and behaviour change. This is a protocol of systematic review to identify the effect of social media interventions on the education and communication among patients affected by cancer. This study aims to reveal the steps of conducting research that systematically reviews all studies for the specific objective. This study aims to examine the social media interventions to improve awareness and knowledge about the disease for patients with cancer and improve communication among them.Methods and analysis This protocol is reported in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols checklist. We will include experimental design studies that report the effect of social media interventions on education and communication among patients with cancer or malignancy and any stage of the disease. Interventions will be inclusive, using all social network platforms for patients' communication and education. We will search PubMed, Web of Science, Scopus and the Cochrane Library from inception until 23 May 2022. Two independent reviewers will screen titles, abstracts and full-text articles with conflicts resolved through discussion or by a third reviewer, as needed. All titles, abstracts and full-text papers will be reviewed independently by two reviewers according to the inclusion and exclusion criteria. Discrepancies will resolve by discussion or SRNK if needed. The two reviewers will also independently complete risk of bias assessments for each included study. The descriptive analysis, including frequency and percentage parameters, will be calculated based on the study’s variables. Furthermore, we will report the results of the quality assessment of studies in table format. In the result section, a narrative synthesis will be applied to describe and compare the paper’s results.Ethics and dissemination Ethics approval will not be needed because the data to be used in this systematic review and meta-analysis will be extracted from published studies. It will be disseminated by publication in a peer-reviewed journal.PROSPERO registration number CRD42022334691.